C-Reactive Protein Apheresis as Anti-inflammatory Therapy in Acute Myocardial Infarction: Results of the CAMI-1 Study - Ries, Wolfgang; Torzewski, Jan; Heigl, Franz; Pfluecke, Christian; Kelle, Sebastian; Darius, Harald; Ince, Hueseyin; Mitzner, Steffen; Nordbeck, Peter; Butter, Christian; Skarabis, Horst; Sheriff, Ahmed; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: C-reactive protein (CRP) is a well-known marker of inflammation. It is less known that CRP mediates tissue damage in acute myocardial infarction (AMI) thus potentially worsening prognosis. A newly developed specific CRP adsorber allows efficient lowering of CRP levels and may improve survival. Objectives: Aim of this multi-center, controlled, non-randomized first-in-man CRP apheresis in Acute Myocardial Infarction study (CAMI-1) was to investigate the relationship between CRP levels (CRP gradient), myocardial infarct size and function as well as safety and efficacy of CRP apheresis in the setting of acute ST-segment Elevation Myocardial Infarction (STEMI) in humans. Methods: Eighty-three patients (45 apheresis, 38 controls) were recruited. CRP apheresis was performed 24 ± 12, 48 ± 12, and optionally 72 ± 12 h after onset of symptoms. First aphereses were performed at a median CRP concentration of 23.0 mg/L (range 9–279). In each apheresis session, 5,900 ± 400 mL plasma was processed via peripheral venous access. Primary study endpoint was a reduction in myocardial infarct size after STEMI as determined by cardiovascular magnetic resonance (CMR). Results: In controls, the CRP concentration significantly correlated with infarct size (p = 0.002) and decreased myocardial function (p ≤ 0.001). The CRP concentration in apheresis patients did not correlate with infarct size (p = 0.66) or left ventricular (LV) function (p = 0.79) and global strains and therefore significantly differed from controls (p = 0.03 and p = 0.002). Three major adverse cardiac events occurred in the control group after 12 months, none occurred in the apheresis group. Mean CRP depletion achieved over all apheresis procedures was 53.0 ± 15.1%. Apheresis sessions were well-tolerated. Reduced infarct size in the apheresis group compared to the control group (primary endpoint) was not achieved according to the original statistical analysis plan. Taking into account the individual CRP levels, however, revealed significant results. Modifications of the analysis plan were introduced in order to recruit a sufficient number of patients. Conclusions: This pilot study in humans reveals a correlation between CRP concentration and myocardial infarct size. CRP concentrations in STEMI can effectively be reduced by CRP apheresis without relevant side effects. CRP apheresis has the potential to interfere with deleterious aspects of STEMI. By lowering CRP levels, it resulted in the loss of correlation of CRP concentrations with myocardial infarct sizes as well as LV function. These results encourage a larger, randomized clinical trial. Clinical Trial Registration:https://www.drks.de/drks_web/navigate.do?navigationId=trial.HTML&TRIAL_ID=DRKS00008988, DRKS00008988.